2015
DOI: 10.4103/1319-3767.153819
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness of colorectal cancer in Saudi Arabia: A survey of 1070 participants in Riyadh

Abstract: Background/Aims:The aim of this study was to investigate colorectal cancer (CRC) awareness in healthy individuals in Saudi Arabia in order to identify segments of the population that would most benefit from targeted education programs.Setting and Design:Survey/questionnaire.Patients and Methods:Random, healthy individuals from Riyadh, Saudi Arabia, were approached to participate in a 10-question multiple choice survey about CRC. Data were analyzed by demographic criteria, including age, gender, marital status,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
74
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 20 publications
(22 reference statements)
10
74
1
1
Order By: Relevance
“…Our results were in disagreement with a couple of studies including alocal study among the general public that revealed a better awareness of CRC symptoms among women. 5,12 The fact that Saudi men in our study showed higher awareness is encouraging especially that previous studies have also shown that CRC is more common among Saudi males. 17,18 Older patients showed higher knowledge of symptoms than younger patients especially in bleeding per rectum and fatigue, they have also shown better knowledge in some risk factors like obesity which is reassuring because they are at higher risk and in need to correctly recognize these symptoms and risk factors.…”
Section: Discussion:-supporting
confidence: 50%
See 2 more Smart Citations
“…Our results were in disagreement with a couple of studies including alocal study among the general public that revealed a better awareness of CRC symptoms among women. 5,12 The fact that Saudi men in our study showed higher awareness is encouraging especially that previous studies have also shown that CRC is more common among Saudi males. 17,18 Older patients showed higher knowledge of symptoms than younger patients especially in bleeding per rectum and fatigue, they have also shown better knowledge in some risk factors like obesity which is reassuring because they are at higher risk and in need to correctly recognize these symptoms and risk factors.…”
Section: Discussion:-supporting
confidence: 50%
“…12 The most recalled symptom of CRC without prompt by Saudi patients was abdominal pain. Likewise, a Malaysian study among rural population reported that abdominal pain was the most frequent symptom identified unaided and the second most agreed symptom of CRC from prompted question.…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Less than 20% of all respondents believe that polyps are a risk factor for CRC, which varied significantly according to level of education; however, even the most educated answered correctly less than 50% of the time. Similarly, only 34.8% of all respondents knew that a family history of CRC imparted a personal risk for CRC [27]. In another study included 371 participants, of whom 52%, 86% and 60%, didn't hear about early screening of CRC didn't perform screened of CRC and didn't know where to screen for colorectal cancer, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that although older individuals and those with higher education tended to answer questions correctly more often, there were some misconceptions regarding universally accepted screening protocols, symptoms, and general understanding of CRC in Saudi Arabia. A national education/ screening program in Saudi Arabia is recommended to improve CRC knowledge [26].…”
Section: Discussionmentioning
confidence: 99%